Field bean for forage and grain in short-season rainfed Mediterranean conditions - Mariotti, Marco; Andreuccetti, Victoria; Arduini, Iduna; Minieri, Sara; Pampana, Silvia (Italian Journal of Agronomy, 2018)
The research was carried out to evaluate the growth rate, the evolution of the nutrient characteristics, and the best stage to obtain the highest yield of nutrients from field bean (Vicia faba var. minor Beck) sown in spring for forage and seed. The best models for quanti-qualitative parameter estimation were curvilinear, such as the one proposed by Hoerl with type y = A xB eCx, and linear, using the sum of the growing degree days (GDD) as the climatic variable. The lengths of both the whole biological cycle and the individual phases of the field bean cycle were related to the amount of GDD of the growing environment and were not affected by the cultivation year. Forage dry matter and nutrient yield of the field bean followed a curvilinear model, while the main quality characteristics followed a linear model over the measured GDD. The highest nutrient and forage yields were not reached at the same time. The highest crude protein, total digestible nutrients and forage dry matter (DM) yields were obtained, at approximately 1230, 1290 and 1360 GDD respectively, when the plants were at stages from the pods being visible in the middle of inflorescence to the end of the pod development. The varieties used in this study presented a similar precocity but a very different productivity. Italian varieties, of which Scuro di Torrelama was the best, produced more than the French variety. With the most productive variety, almost 7 t/ha of forage DM, almost 1.2 t/ha of CP and more than 1.3 t/ha of TDN were obtained. At the GDD of maximum forage production, the CP concentration of the field bean varied from 16 to 18%, EE from 0.6 to 0.7%, NDF from 56 to 58%, RFV from 83 to 94%, TDN from 41 to 48%, and NEL from 1.0 to 1.2 Mcal kg-1. The effects of advanced or delayed harvests, compared to those carried out at the maximum yield stage, are discussed. Grain yield, which reached a maximum of 1.9 t/ha DM, 0.56 t CP/ha and 1.5 t TDN/ha, was mainly limited by a reduced seed filling stage.